Severe, Malignant Acanthosis Nigricans Associated with Adenocarcinoma of the Endometrium in a Young Obese Female - Jacqueline Deen; Thomas Moloney; David Burdon-Jones (Karger Publishers, 2017)
Acanthosis nigricans (AN) is a dermatopathy associated with insulin-resistance, drugs, endocrine disorders, chromosomal abnormalities (benign AN), and neoplasia (malignant AN). Malignant AN (MAN) is a rare paraneoplastic skin syndrome most commonly associated with gastric adenocarcinoma and other intra-abdominal malignancies. We report the case of a 28-year-old female with AN associated with obesity, insulin resistance, and endometrial adenocarcinoma. Although rare, MAN is often an initial sign of malignancy and must trigger extensive investigation, particularly in patients with sudden development of possibly paraneoplastic dermatoses or in patients diagnosed with benign AN with any atypical features.